Evaluation of Salacca sumatrana as soil conservation crop in South Tapanuli, North Sumatra, Indonesia - YUSRIANI NASUTION (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Nasution Y, Rasyidin A, Yulnafatmawita, Saidi A. 2019. Evaluation of Salacca sumatrana as soil conservation crop in South Tapanuli, North Sumatra, Indonesia. Biodiversitas 20: 664-670. Salacca sumatrana Becc (snake fruit; or ‘Salak' in local name) is a profitable commodity. Morphologically, it is characterized by low, wide canopy that is potential intercept rainfall, while its roots are able to withstand soil erosion. This study is aimed to evaluate one variety of S. sumatrana named ‘salak sidimpuan" as commodity crop soil conservation based on its capability to intercept rain and trap soil sediment in the catchment area of S. sumatrana field. The research was conducted on mineral soils at West Angkola Sub-district, South Tapanuli District, North Sumatra Province, Indonesia with an altitude of 350-880 m above sea level. The study was carried out from October 2016 until March 2017 using survey method to calculate on rainfall interception, stemflow and throughfall while measurement of sediment used evaporation method. Statistical analysis was used to observe the difference of sediment trapped on the catchment area of S. sumatrana agroforest and the catchment area of mixed forest using Mann-Whitney Test. The results show that rainfall interception on S. sumatrana agroforest is 74.33% of the average rainfall while the Mann-Whitney Test Sig (2-tailed) is 0.000, indicating significant difference in trapping soil sediment between S. sumatrana agroforest and mixed forest. The amount of soil erosion on the catchment of S. sumatrana agroforest is 15.12 ton/ha/year while the erosion on mixed forest is 194.85 ton/ha/year. Thus S. sumatrana plant is capable to withstand rain interception with the result that soil erosion can be held in the catchment area of S. sumatrana agroforest. Instead of the calculation rain interception and soil erosion, then S sumatrana is classified as a soil conservation crop.